PERBEDAAN PERCEPATAN PENYEMBUHAN PERAWATAN LUKA BERSIH DENGAN MENGGUNAKAN SODIUM KLORIDA 0,9% DAN POVIDONE IODINE 10% PADA PASIEN SECTIO CAESARIA - Fitriana Rakhimah (Sekolah Tinggi Pariwisata Mataram, 2023)
Surgery is an invasive action performed by the medical team to overcome medical problems. The result that arises is the presence of postoperative wounds in patients. The wound healing process can be fast or slow. It depends on many factors, including the presence of infection, nutritional status, the state of the wound itself, and the administration of medications. Various opinions on wound care are often discussed, especially wound care cleaned with sodium chloride and povidine iodine 10%, but the reactions caused by these materials have not been widely discussed. Wound care using antiseptics is more familiar and frequently practiced. In some hospitals, wound care using 0.9% sodium chloride has been developed, but the mechanism of this material has not been explained. Objective: To compare the effect of wound treatment with 0.9% sodium chloride and 10% povidine iodine on accelerating wound healing. Methods: Quasy-Experiment (Post-Test Control Group Design) to find the effect of dependent and independent variables. This study was conducted on all post-cesarean section patients who were treated in the delivery room of Dr. Soebandi Jember Hospital. The population obtained was about 20 respondents. The results of wound treatment using sodium chloride 0.9% who experienced rapid healing were 40% of the total sample. While slow healing occurs in samples treated with povidine iodine 10%, amounting to 20% of the total sample. Then through the Fisher's Exact Test, the results obtained p = 0.628 indicate that there is no significant difference in wound care using sodium chloride 0.9% and povidine iodine 10% on the acceleration of wound healing.Suggestion: To be able to get a clear picture of the benefits of wound care using 0.9% sodium chloride and 10% povidine iodine to accelerate wound healing, further research needs to be done on the effect of wound care using more specific materials